1975
DOI: 10.1289/ehp.7510151
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals in occupationally and nonoccupationally exposed individuals.

Abstract: An epidemiological survey was conducted in Houston, Texas on five trace metals in policemen, parking garage attendants, women living near freeways and three control groups of subjects. The controls were matched with the exposed groups for covariate information such as age, sex, smoking habits, ethnic background, socioeconomic status, hair color, and education. Each subject was sampled four times for blood, urine, hair, and feces, and these samples were analyzed for lead, cadmium, zinc, manganese, and copper. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

1975
1975
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…Health effects of exposure to platinum and palladium reviewed in a previous study (1) indicated that soluble forms of platinum can create allergic responses in sensitive individuals. The catalysts used small quantities of platinum and palladium, and there have been some indications of emissions of particles of these metals.…”
Section: Introductionmentioning
confidence: 99%
“…Health effects of exposure to platinum and palladium reviewed in a previous study (1) indicated that soluble forms of platinum can create allergic responses in sensitive individuals. The catalysts used small quantities of platinum and palladium, and there have been some indications of emissions of particles of these metals.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Krom s›n›r de¤eri için CDC'nin kaynaklaArda Sürücü H ve ark. | Otopark çal›flanlar›nda kan kurflun, kadmiyum, krom ve total antioksidan düzeyinin de¤erlendirilmesi r›nda yan etki görülebilen en üst de¤er al›nd›.…”
Section: Tan›mlamalarunclassified
“…Johnson ve arkadafllar› egzoz gaz›na maruz kalanlarda, EPA de¤e-ri benzeri ya da daha yüksek sonuçlar (trafik polislerinde %6, kontrollerde %2, otopark çal›flanlar›nda %16, otopark çal›flanlar› kontrol grubunda %3) elde etmifllerdir. [3] Mormontory ve arkadafllar› da benzer flekilde, trafik polislerindeki kan kurflun düzeyini 44.7, μg/dl, ofiste çal›flan polislerin kan kurflun düzeyini ise 39.3 μg/dl bulmufllard›r. [10] Yine Kara ve arkadafllar›n›n Adana'da trafik polislerinde yapt›¤› çal›flmada kan kurflun düzeyi dikkat çeki-ci olarak yüksek oldu¤u saptanm›flt›r.…”
Section: Tan›mlamalarunclassified
See 1 more Smart Citation
“…Hair samples are easy to obtain, heavy metal analysis of hair is precise, and numerous studies show that hair metal concentrations accurately reflect exposure to metal pollutants (Nishiyama and Nordberg, 1972;Sorenson, Melby, Nord, & Petering, 1973;Corridan, 1974;Reeves, Jolley, & Buckley, 1975;Johnson, Tillery, and Prevost, 1975;Oleru, 1976;Chatt, Roberts, and Jervis, 1977). Blood primarily reflects the acute effects of recent exposure to metals, whereas hair incorporates lead from the body over longer periods of time and thus is a more sensitive indicator of long-term exposure to low levels of metals than is blood (Gordon, 1976).…”
Section: Implications For School Practicesmentioning
confidence: 99%